Assessment of climate change impact on thermal bioclimatic indicators in a tropical region with the climate projections from CMIP6 modele dynamics - Kamruzzaman, Mohammad; Islam, H. M. Touhidul; Ahmed, Sharif; Bhattacharjya, Debu Kumar; Khan, Md. Shah Kamal; Mahmud, Golam Iftekhar; Shahid, Shamsuddin (Research Square Platform LLC, 2023)
The global mean surface temperature is expected to continue to rise as a result of climate change. However, the effects of this transformation are not uniformly distributed across the globe, making regional analysis essential. As a monsoon region with tropical and low-lying terrain, Bangladesh is especially susceptible to the effects of climate change. Despite this, no effort has been made to evaluate the potential changes in thermal bioclimatic indicators (TBIs) in practical applications, which is crucial. Using a multi-model ensemble (MME) of 18 CMIP6 GCMs, this study projected the variations in 11 TBIs across Bangladesh for the near (2015–2044), mid (2045–2074), and far (2075–2100) futures under three SSPs: low (SSP126), medium (SSP245), and high (SSP585). The study revealed that in the future, the average annual temperature in Bangladesh will increase by 0.62 to 1.85°C for SSP126, by 0.51 to 2.81°C for SSP245, and by 0.54 to 4.88°C for SSP585, indicating a rise in temperature that is consistent with the global average. In addition, the study predicted that the diurnal temperature range (DTR) could decrease by -0.17 to -2.50°C, and that isothermality could decrease by as much as -0.30% at many stations. The projected temperature rise would be highly variable, ranging from 0.14 to 0.39°C in the northeast and southeast to 0.17 to 2.66°C in the northwestern, central, and southwestern regions. In addition, the study revealed a considerable increase in average temperature between the coldest and warmest quarters. The average temperature would increase significantly more in the drier quarter than in the wettest quarter. These findings are crucial for establishing mitigation goals and adapting to climate change in Bangladesh, underscoring the urgency of taking the necessary steps to combat the negative effects of global warming.